Mastery Through Practice: Exploring the Apprenticeship-Based Learning for Skills Acquisition, Sustained Engagement, and Lifelong Learning - Chibueze Tobias Orji (International Journal of Home Economics, Hospitality and Allied Research, 2025)
Apprenticeship-based learning has long been recognised as an effective practical approach for skill acquisition; however, its potential impact on lifelong learning and sustained engagement remains underexplored. This study examined the experiences of apprentices enrolled in community-based skill acquisition programmes, with particular attention to their technical skill development, ongoing engagement, and attitudes towards lifelong learning. Semi-structured interviews and focus group discussions were conducted with 17 apprentices aged 20 to 30, representing various trades across Nigeria’s South-East and South-South regions. A thematic analysis revealed three central themes: learning by doing, sustained engagement facilitated by autonomy and mentorship, and apprenticeship serving as a foundation for lifelong learning. The results offer valuable insights into enhancing apprenticeship programmes, highlighting their role not only in developing technical expertise but also in fostering critical soft skills and a commitment to continuous self-improvement. These findings can inform vocational training institutions, policymakers, and programme administrators aiming to optimise apprenticeship initiatives. While the qualitative approach of this study provides detailed, context-rich perspectives, future research adopting a mixed-methods design could further illuminate broader patterns and trends.